Sustainable Operations Management: Key Practices And Cases - Nunes, Breno; Batistia, Luciano and Masi, Donato (London Routledge, 2023)
"Sustainable Operations Management applies the issues of sustainability to all strategic decisions of operations: capacity management, supply network, process technology, and development and organisation. This book extends the existing literature of operations management that for years has been paramount in creating economic value with little consideration of environment and social dimensions. Whilst based on robust theoretical frameworks, some developed by its own authors, the book is enriched by international case studies and real-world illustrations throughout, to demonstrate how this theory translates to practice. Each chapter begins with learning objectives and ends with a summary, activity and questions for discussion. Readers will gain a comprehensive and in-depth knowledge on how to manage operations for sustainability. They will learn the ways to formulate a sustainable operations strategy and the elements involved in managing tactical and operational activities to enhance sustainability performance over time. The book covers all aspects of the new business sustainability paradigm from an operations perspective, including sustainable development goals, the circular economy, digital transformation, and organisational structures. With international agreements and national policies in place around themes such as climate change, ocean plastic pollution, loss of biodiversity, water scarcity, and zero landfill targets, this book will be a must for any university abiding to the Principles of Responsible Management Education (PRIME). The text is suitable mostly for MSc and MBA students on sustainable supply chain and operations management modules as well as broader Operations Management courses, but it can also be used for final-year Undergraduate students as part of advanced operations management modules. Online resources include chapter-by-chapter PowerPoint slides and a test bank of questions"--
Includes bibliographical references and index.
Keywords: Industrial Management; Production Management; Sustainable Development